Morphophysiological Analysis of Growth and Yield in Cashew (Anacardium Occidentale L.) - Pushpalatha P B (Department of Plantation Crops And Spices,College of Horticulture, 2000)
The present investigation “Morphophysiological analysis of growth and yield in cashew (Anacardium occidentale L.)” was carried out with the objectives to study the variability in morphological characters among cashew genotypes, to elucidate the factors associated with yield, to analyse the variability in biochemical and anatomical characters among varieties at different physiological stages of reproductive growth, to explore the possibilities of chemical regulation of flowering and to control tree size through induction of dwarfism in cashew grafts at nursery stage. Grouping of 67 genotypes based on flowering behaviour and yield performance was done. Studies on variability in 18 morphological characters among 27 genotypes showed high variability for flush length, number of leaves per flush, percentage of hermaphrodite flowers, number of nuts per panicle, nut weight and yield. Correlation studies revealed that yield is positively correlated with number of panicles (m-2), hermaphrodite flowers (%), panicle length and number of nuts per panicle and negatively correlated with flush length. The presence of carbohydrate, nitrogen and chlorophyll in mature lateral shoots before flushing and in reproductive flushes after panicle development is found to determine the yield potential of cashew trees. High activity of the enzyme Nitrate Reductase was found necessary to impart better nitrogen use efficiency to cashew plants. Studies on anatomical features of mature lateral shoots of different yield groups showed that thick bark and greater number of xylem vessels per unit area are the two characters associated with high yielders. The distinct feature of reproductive flushes from vegetative flushes was the presence of a clear flowering primordia in them, before panicle emergence. Foliar application of cultar at the rate of 1000 mg 1-1 in combination with KNO3 one percent and carbaryl 0.10 per cent was effective in regulating flowering behaviour of cashew varieties and manipulating the yield contributing factors favourably. Late season varieties showed maximum response to chemical regulation of flowering. Soil application of cultar to the grafts at the rate of 2 ml per plant, twice, first at one month and second at three months after sprouting was found effective in inducing dwarfism at nursery stage. The anatomical features associated with dwarfism viz., bark thickness and number of xylem vessels per unit area in lateral shoots was found increased in response to soil application of cultar to the grafts.